Efficacy and safety of 3‐n‐butylphthalide combined with endovascular treatment in acute ischemic stroke due to large vessel occlusion. (2nd October 2022) - Liu, Shuai; Li, Fengli; Yang, Jie; Xie, Dongjie; Yue, Chengsong; Luo, Weidong; Hu, Jinrong; Song, Jiaxing; Li, Linyu; Huang, Jiacheng; Zhao, Chenhao; Gong, Zili; et al.
Abstract: Background: The drug 3‐ n ‐butylphthalide (NBP) was developed and approved in China, where it has been used to treat ischemic cerebrovascular diseases. It is also considered to have a neuroprotective effect. This study aimed to evaluate whether NBP combined with endovascular treatment (EVT) can improve the clinical outcome and safety in patients with acute ischemic stroke (AIS) due to large vessel occlusion (LVO). Methods: Data from three studies of patients treated with EVT for AIS due to LVO were combined in this study. Patients of LVO undergoing EVT were dichotomized into NBP and non‐NBP subgroups. The primary efficacy outcome was the shift of the modified Rankin Scale (mRS) score at 90 days. The secondary efficacy outcome included favorable functional outcomes, functional independence, and excellent outcome (defined as an mRS score of 3 or less) at 90 days. Safety outcomes included mortality within 90 days and symptomatic intracranial hemorrhage (sICH) within 48 h. Results: A total of 1820 patients undergoing EVT were included in this study; 628 (37.5%) patients received NBP treatment, whereas 1138 (62.5%) did not. After adjusting for multiple factors, NBP was associated with the improvement of functional outcomes at 90 days (adjusted common odds ratio [OR]: 1.503; 95% confidence interval (CI): 1.254–1.801; p  < 0.001). NBP was associated with a higher rate of 90‐day favorable outcomes (adjusted OR: 1.589; 95% CI: 1.251–2.020; p  < 0.001) and a lower rate of 90‐day mortality (adjusted OR: 0.486 [95% CI: 0.372–0.635]; p  < 0.001). sICH occurred in 74 of 682 (10.9%) patients in the NBP group and 155 of 1126 (13.8%) patients in the non‐NBP group; no statistical difference was detected (adjusted OR: 0.787 [95% CI: 0.567–1.092]; p  = 0.152). Conclusion: Among patients with AIS due to LVO, NBP combined with EVT is associated with better functional outcomes and reduced mortality risk without increasing the risk of sICH. Abstract : Among patients with acute ischemic stroke due to LVO， butylphthalide combined with EVT is associated with better functional outcomes and reduced mortality risk without increasing the risk of symptomatic intracranial hemorrhage.